The utilization of quality improvements in public health systems across asian countries: A systematic review - Rudi Nasib; Nelson Lean Boon Leong; Muhammad Mudassir Abdul Rahim; Nachia Banu Abdul Rahim; Nabihah Ali; Mohd Ihsanuddin Abas; Amirah Azzer; Hafiz Jaafar; Mursid Raharjo; Nur Ezdiani Mohamed; Abdul Rahman Ramdzan (Universiti Putera Malaysia, 2023)
Public health leaders in the current scenario face the persistent task of providing efficient public health services, which is made even more challenging due to the limitations imposed by scarce resources. To overcome the issue, various quality improvements (QI) were implemented to improve the efficacy and effectiveness of public health programs, services, and organisations. Objective: The review aimed to identify and examine published studies implementing QI within Asian public healthcare systems and their benefits on healthcare performance. Methods: The systematic review followed the PRISMA guidelines. A comprehensive search was conducted across three databases - PubMed, SCOPUS, and Cochrane - specifically targeting peer-reviewed articles with titles or abstracts related to QI in the public health system. Only papers published between January 2017 and January 2022 were considered for inclusion in the review. Results: Nine articles were identified as relevant to the topic of interest, and the extracted findings were analysed. These nine studies naturally fell into distinct categories of QI, namely the Quality Improvement Model, Key Performance Index, Clinical Audit, and Root Cause Analysis. These studies explicitly connected their implemented QI to enhancing healthcare delivery quality. Conclusion: The findings of the review demonstrated that the implementation of QI could lead to notable enhancements in both the quality of care and overall healthcare performance.